Understanding the role of nerves in head and neck cancers - a review - Krzysztof Rutkowski; Michał Gola; Michał Gola; Janusz Godlewski; Janusz Godlewski; Anna Starzyńska; Anna Starzyńska; Giulia Marvaso; Giulia Marvaso; Federico Mastroleo; Federico Mastroleo; Maria Giulia Vincini; et al. (Oncology Reviews)
Worldwide, head and neck cancers (HNCs) account for approximately 900,000 cases and 500,000 deaths annually, with their incidence continuing to rise. Carcinogenesis is a complex, multidimensional molecular process leading to cancer development, and in recent years, the role of nerves in the pathogenesis of various malignancies has been increasingly recognized. Thanks to the abundant innervation of the head and neck region, peripheral nervous system has gained considerable interest for its possible role in the development and progression of HNCs. Intratumoral parasympathetic, sympathetic, and sensory nerve fibers are emerging as key players and potential targets for novel anti-cancer and pain-relieving medications in different tumors, including HNCs. This review explores nerve-cancer interactions, including perineural invasion (PNI), cancer-related axonogenesis, neurogenesis, and nerve reprogramming, with an emphasis on their molecular mechanisms, mediators and clinical implications. PNI, an adverse histopathologic feature, has been widely investigated in HNCs. However, its prognostic value remains debated due to inconsistent results when classified dichotomously (present/absent). Emerging evidence suggests that quantitative and qualitative descriptions of PNI may better reflect its clinical usefulness. The review also examines therapies targeting nerve-cancer crosstalk and highlights the influence of HPV status on tumor innervation. By synthesizing current knowledge, challenges, and future perspectives, this review offers insights into the molecular basis of nerve involvement in HNCs and the potential for novel therapeutic approaches.